Pengaruh Model Pembelajaran Savi (Somatic, Auditori, Visual, Intelektual) Berbantuan Media Mind Mapping Terhadap Minat Belajar IPA Kelas IV - Siti Ayuni Shaharo; Atikah Syamsi; Nur Atikoh (Prodi PGSD Unsultra, 2024)
This study aims to analyze the effect of the Savi learning model assisted by mind mapping media on the interest in learning science for fourth grade students at MI Miftahul Ulum Karangsari. Using a quantitative approach with a quasi-experimental design, this study involved two groups, namely the experimental group that applied the Savi learning model and the control group that used the conventional learning model. Data collection used observation and questionnaires. The results showed that the Savi learning model had a significant positive impact on increasing students' interest in learning. The experimental group showed an interest in learning of (average 45.6) compared to the control group showing an interest in learning of (average 38.4). This shows the potential to increase interest in learning science using the Savi learning model assisted by mind mapping media.